Trade and security, I: anarchy - Anderson, James E. 1943-; Marcouiller, Douglas (NBER working paper series, 1997)
Market exchange is subject to an endogenously determined level of predation which impedes specialization and gains from trade. We construct a model in which utility-maximizing agents opt between careers in production and careers in predation. Three types of equilibria may emerge: autarky (with no predation and no defense), insecure exchange equilibria (with predation and defense), and secure exchange equilibria (in which defense completely deters predation). Trading equilibria, two-thirds of them secure, are supported only in a narrow range of security parameter values. Since changes in the technologies of defense and predation have terms of trade effects, some producers may be hurt by enhanced security. We show cases of immiserizing security' in which producers in large poor countries are harmed by increased security.